Opportunities For Direct Foreign Investment in Small Industrial Zones in The Context of Economic Modernization: Peluang Investasi Asing Langsung di Kawasan Industri Kecil dalam Rangka Modernisasi Ekonomi - Halimzhanov Dilshod Ergashbekovich (Universitas Muhammadiyah Sidoarjo, 2024)
At the present stage of the development of the world economy, the development of economic policy features that contribute to the socio-economic sustainable development of regions and their radical implementation into real life is becoming increasingly important every day. Increasing the possibilities of attracting foreign direct investment in the spheres and sectors of the economy, modernization of industrial enterprises, introduction of advanced foreign equipment and technologies into production is largely due to the creation of special economic zones, including small industrial ones. Based on this, the chosen research topic is becoming relevant today. Highlights: Strengthen economic zones for sustainable regional development and foreign investment. Promote innovation, tech upgrades, and public-private partnerships in industrial zones. Enhance investor protection, legal frameworks, and skilled workforce for economic growth. Keywords: investments, investment policy, structural policy, industrialization, modernization, foreign investments, special economic zone, industrial zone, small industrial zone, youth industrial zone.